Thresholds in the Finance-Growth Nexus : A Cross-Country Analysis - Yilmazkuday, Hakan (World Bank, 2013)
Thresholds of inflation, government size, trade openness, and per capita income for the finance-growth nexus are investigated using five-year averages of standard variables for 84 countries from 1965 to 2004. The results suggest that (i) high inflation crowds out positive effects of financial depth on long-run growth, (ii) small government sizes hurt the finance-growth nexus in low-income countries, while large government sizes hurt high-income countries, (iii) low levels of trade openness are sufficient for finance-growth nexus in high-income countries, but low-income countries need higher levels of trade openness for similar magnitudes of the finance-growth nexus, (iv) catch-up effects through the finance-growth nexus are higher for moderate per capita income levels.